Microwave-assisted synthesis of multiply-twinned Au–Ag nanocrystals on reduced graphene oxide for high catalytic performance towards hydrogen evolution reaction. Issue 10 (17th February 2016) - Qin, Yuchen; Dai, Xiaoping; Zhang, Xin; Huang, Xingliang; Sun, Hui; Gao, Daowei; Yu, Yanbing; Zhang, Pengfang; Jiang, Yan; Zhuo, Hongying; Jin, Axiang; Wang, Hai
Abstract : Multiply-twinned Au–Ag NCs/rGO are prepared by a one-pot method under microwave irradiation and exhibit excellent HER activity and stability. Abstract : Nanocrystals (NCs) with a multiply-twinned structure possess great potential in the field of electrocatalysis. Reduced graphene oxide (rGO) has been employed as a support to further improve the stability and activity of catalysts. However, the twinned structure is thermodynamically unstable due to the high total free energy, and it is difficult to control the shape of the crystals during preparation, especially when grown directly on the surface of rGO. Herein, multiply-twinned structural Au–Ag decahedra and icosahedra were grown directly in situ on rGO through a facile approach under microwave irradiation. Thanks to the synergy of abundant twin defects and the electronic effect of the intimate contact/interaction between the Au–Ag alloy and the rGO, these as-prepared Au–Ag NCs/rGO hybrids exhibit excellent activity and stability towards the hydrogen evolution reaction. In particular, Au–Ag icosahedra/rGO exhibits Pt-like electrocatalytic activity and enhanced stability compared to commercial Pt/C.